Biomedical Agriculture A Transdisciplinary Approach - S., Neenu; Meena, B. P.; Mandal, Asit; Biswas, A. K.; Rao, A. Subba (Indian Farming, 2016)
Half of the world population continues to be affected by 33 malnutrition and deficiency of essential nutrients. Studies conducted in different parts of the world have shown that dietary patterns emphasizing plant foods are linked to lesser occurrence of chronic diseases. A new, emerging field of biomedical agriculture is developing, through which consumers will be informed about the current, health benefits of existing food selections and also would be offered new selections with improved disease prevention characteristics.